PENERAPAN MODEL TPACK DALAM MENGUBAH MINDSET TERHADAP ZERO DIGITAL DI SEKOLAH - Latuconsina, Najwah; Azizah, Rahma Nurul; Fadilah, Rizki Karimatul; Hafsoh, Zenny Zanuba; Salsabila, Unik Hanifah (Alifbata : Jurnal Pendidikan Dasar, 2025)
This article discusses the application of the TPACK (Technological Pedagogical Content Knowledge) model in school learning. At present, there are still many parents and some schools that still apply zero digital, because they think that technology can have a negative impact on students. The purpose of this research is to show that the use of technology is needed and beneficial in the learning process of students at school. This research uses a qualitative method with a literature study approach. This research utilizes a variety of written sources, including books, scientific journals, institutional reports, and other relevant literature as the primary source of data in the process of collecting information. Although there are challenges in implementing this model, such as limited access to technology and training, teachers succeed in creating an interactive and effective learning environment.